Hemisection with socket preservation using alloplastic bone graft and platelet-rich fibrin - Ismiyatin, Kun; Anindya, Cinitra; Widjaja, Olivia Vivian; Harseno, Singgih; Dzulfiqar, Ahmad Afif; binti Tengku Ahmad Noor, Tengku Natasha Eleena (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: The developments in endodontics have created opportunities for patients to maintain functional teeth for longer. Surgical endodontic treatment, such as hemisection, has become a more conservative treatment than complex treatments, such as removable or fixed partial dentures or implants. Purpose: The aim of this treatment is to preserve the remaining tooth structure through a hemisection procedure and socket preservation using an alloplastic bone graft and platelet-rich fibrin (PRF). Case: A female patient presented with mastication pain and a large carious tooth in the right mandibular first molar and wanted to save the tooth. Examination showed deep caries and perforation in the bifurcation area of the tooth with loss of the distal crown. However, the mesial root could be preserved, thus hemisection was proposed. Case management: A root canal treatment was performed on the mesial root, followed by separation of the mesial and distal roots, and, finally, distal root extraction. A mixture of PRF and bone graft was used for socket preservation. The tooth was restored with a splinted zirconia crown. Conclusion: Hemisection with socket preservation using alloplastic bone graft and PRF represents a more conservative treatment option for molar teeth with extensive caries. This approach exhibits a good long-term prognosis and enhances the bone healing process.